Farrowing to Weaning Temporal Window: Managemental and Nutritional Strategies to Optimize the Piglet Survival - Singh, Mahak; Celina, Apanai; shüya, Pedenuo; Katiyar, Rahul; Bhutia, Pempa Lamu; Rautela, Rupali; Singh, Gyan Dev; Kalita, Homeswar (The Indian Journal of Animal Reproduction, 2026)
The goal of the swine production industry is to produce more pork from fewer pigs, thereby increasing efficiency and sustainability. A systematic review of the management of hyper prolific sows (>16 piglets per farrowing) from the far rowing to the weaning temporal window was the objective to optimize sow and piglets’ survival and consequently their improved lifetime productivity. The search for studies was conducted in May 2025 using the PubMed, ISI Web of Science, ScienceDirect, and Scopus databases. The literature search was conducted using the keywords: pig, swine, sow, farrow ing, piglets, weaning, creep feed, hyper prolific sows, piglet mortality, herbal supplement, and feed additive. Hyper prolific sows have a longer farrowing duration, which requires critical attention. Pre-weaning mortality peaks within 24 hours of farrowing due to factors related to sows, piglets, management, and the environment. Another critical step in a piglet’s life is weaning. Weaning is considered one of the most stressful stages for piglets. Post-weaning, piglets are subjected to environmental, psychological, crowding, and social stressors. Abrupt weaning leads to changes in the gastrointestinal tract (GIT) of the piglets, impaired gut microbiota, and deregulation of the mucosal immune function. Consequently, there will be a decrease in feed intake, occurrence of post-weaning diarrhoea (PWD), post-weaning growth check, and ultimately poor lifetime production performance. These include controlled farrowing, nutrition and management practices, creep feeding, animal welfare, and efficient weaning strategies.